2014
DOI: 10.1016/j.fluid.2014.08.005
|View full text |Cite
|
Sign up to set email alerts
|

Thermophysical properties of sulfonium- and ammonium-based ionic liquids

Abstract: Experimental data for the density, viscosity, refractive index and surface tension of four sulfonium-and ammonium-based Ionic Liquids (ILs) with the common bis (trifluoromethylsulfonyl) . Based on the gathered results and on data taken from literature, the impact of the cation isomerism and of the size of the aliphatic tails, as well as the effect resulting from the substitution of a nitrogen by a sulfur atom as the cation central atom, on the thermophysical properties of sulfonium-and ammonium-based ILs is he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
64
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 101 publications
(84 citation statements)
references
References 94 publications
19
64
1
Order By: Relevance
“…28 The V m of each IL at 298.15 K was determined based on the experimental density data taken from the literature. [37][38][39] As shown in Fig. 4, the sulfonium-based ILs fall close to the correlation previously presented for a wide range of [NTf 2 ]-based ILs.…”
Section: Temperature Dependence Of the Water Solubility In Ilssupporting
confidence: 88%
“…28 The V m of each IL at 298.15 K was determined based on the experimental density data taken from the literature. [37][38][39] As shown in Fig. 4, the sulfonium-based ILs fall close to the correlation previously presented for a wide range of [NTf 2 ]-based ILs.…”
Section: Temperature Dependence Of the Water Solubility In Ilssupporting
confidence: 88%
“…The densities follow a linear dependence with temperature over the range studied and is seen to decrease with increasing cation size; the values found are in good agreement with the literature. 36 Figure S 1).…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…Coutinho et al [20,[24][25][26][27][28][29][30][31][32] found that surface tension in a couple of imidazolium-based IL series decreases with an increase in the cation side alkyl chain length up to hexyl and thus defined the CACL (critical alkyl chain length). On the other hand, surface tension remained almost constant for ILs with aliphatic moieties longer than the obtained CACL.…”
mentioning
confidence: 99%